Necessity is the Mother, but Protection May Not Be the Father of Invention - Endres, A. Bryan; Giffin, Carly E. (Science and Technology Law Review, 2013)
Standard innovation theory assumes that intellectual property protection is a prerequisite to the development of technological advances. A strong intellectual property system, composed of both laws that establish intellectual property protection and a judicial or other adjudicative system to enforce the property right, has been considered necessary to stimulate innovation for the benefit of society. While not directly challenging this traditionally held belief, the authors used empirical data to test the assumption in the context of agriculture. This paper analyzed twenty years of agricultural production data from Argentina, Brazil, China, India, and the United States and their accompanying intellectual property systems. The authors sought to determine whether strong intellectual property laws, along with vigorous enforcement, do in fact correlate with greater innovation. The results of this empirical study were mixed. The authors’ analysis identified a statistically significant relationship between research and development (R & D) expenditures — considered a proxy for innovation — and hectares planted, but found no significant relationship between R & D expenditures and crop yield. Subsequent analysis of applications for intellectual property protection and crop production yielded similarly mixed results. Thus, the analysis reveals that, based on some measures, innovation manages to thrive despite the absence of strong intellectual property regimes in some developing countries.